Genetic variation in the mitochondrial 16S ribosomal RNA gene of Ixodes scapularis (Acari: Ixodidae) - Krakowetz, Chantel N (Parasit Vectors, 2014)
BACKGROUND: Ixodes scapularis is a vector of several human pathogens in the United States, and there is geographical variation in the relative number of persons infected with these pathogens. Geographically isolated populations of I. scapularis have established or are in the process of establishing in southern Canada. Knowledge of the genetic variation within and among these populations may provide insight into their geographical origins in the United States and the potential risk of exposure of Canadians to the different pathogens carried by I. scapularis. METHODS: Part of the mitochondrial (mt) 16S ribosomal (r) RNA gene was amplified by PCR from 582 ticks collected from southern Canada, and Minnesota and Rhode Island in the United States. Sequence variation was examined in relation to the predicted secondary structure of the gene. Genetic diversity among populations was also determined. RESULTS: DNA sequence analyses revealed 52 haplotypes. Most mutational alterations in DNA sequence occurred at unpaired sites or represented partial compensatory base pair changes that maintained the stability of the secondary structure. Significant genetic variation was detected within and among populations in different geographical regions. A greater proportion of the haplotypes of I. scapularis from the Canadian Prairie Provinces were found in the Midwest of the United States than in other regions, whereas more of the haplotypes of I. scapularis from the Canadian Central and Atlantic Provinces occurred in the Northeast of the United States. Nonetheless, 58% of I. scapularis were of a haplotype that occurs in the Midwest and Northeast of the United States; thus, their geographical origins could not be determined. CONCLUSIONS: There is considerable genetic variation in the mt 16S rRNA gene of I. scapularis. There is some evidence to support the hypothesis that some lineages of I. scapularis in the Atlantic and Central Provinces of Canada may be derived from colonizing individuals originating in the Northeast of the United States, whereas those in the Prairie Provinces may be derived from individuals originating in the Midwest of the United States. However, additional genetic markers are needed to test hypotheses concerning the geographical origins of I. scapularis in Canada. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s13071-014-0530-6) contains supplementary material, which is available to authorized users.